Application of blockchain technology in the demand response management of power grid - Haowen REN; Yaqi YANG (Dianxin kexue)
The theory of decentralized blockchain mechanism was studied,and a method of applying distributed block chain technology to manage demand response planning in smart grid environment was proposed.This method was based on the blockchain distributed ledger accounting tamper-proof technology,which stored the energy consumption information collected from the intelligent metering devices of the IoT,and defined the self-executing intelligent contract at each consumer level in a programmatic way to ensure the flexibility of transactions.Blockchain distributed technologies provided incentives or penalties to balance energy demand with grid energy production rules.Consensus-based validation would be used to validate demand response plans and provide appropriate financial settlement for flexible suppliers.The results show that the power demand side management based on blockchain distributed technology can be used to match energy demand and production under the condition of smart grid,with high accuracy of demand response signal,but less flexibility required for convergence.